Effects of mindfulness on meta-awareness and specificity of describing prodromal symptoms in suicidal depression. - Hargus, E; Crane, C; Barnhofer, T; Williams, J (2010)
The authors examined the effects of mindfulness training on 2 aspects of mode of processing in depressed participants: degree of meta-awareness and specificity of memory. Each of these has been suggested as a maladaptive aspect of a mode of processing linked to persistence and recurrence of symptoms. Twenty-seven depressed participants, all of whom had experienced suicidal crises, described warning signs for their last crisis. These descriptions were blind-rated independently for meta-awareness and specificity. Participants were then randomly allocated to receive mindfulness-based cognitive therapy (MBCT) plus treatment as usual (TAU) or TAU alone, and retested after 3 months. Results showed that, although comparable at baseline, patients randomized to MBCT displayed significant posttreatment differences in meta-awareness and specificity compared with TAU patients. These results suggest that mindfulness training may enable patients to reflect on memories of previous crises in a detailed and decentered way, allowing them to relate to such experiences in a way that is likely to be helpful in preventing future relapses.